2007
DOI: 10.1080/00036840500427478
|View full text |Cite
|
Sign up to set email alerts
|

Options-based forecasts of futures prices in the presence of limit moves

Abstract: The reported analysis examines a simultaneous estimation option-based approach to forecast futures prices in the presence of daily price limit moves. The procedure explicitly allows for changing implied volatilities by estimating the implied futures price and the implied volatility simultaneously. Using futures and futures options data for three agricultural commodities, it is found that the simultaneous estimation approach accounts for the abrupt changes in implied volatility associated with limit moves and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…2 In addition to being a forward-looking measure of market impact, another advantage of implied volatility is that option price changes are either exempt from price limits or rarely impacted by price limits (due to delta effects). Limit moves in futures prices generally are associated with the arrival of new information and the resolution of large amounts of uncertainty (Egelkraut, Garcia, & Sherrick, 2007). Since on limit move days futures prices do not reflect the ''true'' or ''full'' market reaction to new information, the use of futures prices to measure the impact of scheduled news announcements may result in downward-biased estimates of impact.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to being a forward-looking measure of market impact, another advantage of implied volatility is that option price changes are either exempt from price limits or rarely impacted by price limits (due to delta effects). Limit moves in futures prices generally are associated with the arrival of new information and the resolution of large amounts of uncertainty (Egelkraut, Garcia, & Sherrick, 2007). Since on limit move days futures prices do not reflect the ''true'' or ''full'' market reaction to new information, the use of futures prices to measure the impact of scheduled news announcements may result in downward-biased estimates of impact.…”
Section: Introductionmentioning
confidence: 99%
“…Poteshman (2000) suggested that a portion of the apparent bias in the Black-Scholes model may be attributed to the measurement errors in realized volatility. Egelkraut et al (2007) found that the simultaneous estimation approach accounts for the abrupt changes in implied volatility associated with limit moves and generates more accurate price forecast than conventional methods that rely only on implied variable. Maris et al (2007) pointed out that successful volatility forecasts in terms of directional accuracy was found to be sufficient for positive results.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Following the method proposed by Egelkraut et al (2007), we estimate the options‐implied futures price Ftruêd,c using intraday options transactions observed when the underlying futures contract is locked at the limit 13 . Because no limits are imposed on the options contract, its price can continue to adjust on locked‐limit days even though the futures price remains bounded for the current trading day.…”
Section: Measuring Market Activities Around Limit Movesmentioning
confidence: 99%